INOVASI SOSIAL PETERNAKAN RAKYAT SEBAGAI IMPLEMENTASI ASTA CITA DALAM PEMBERDAYAAN EKONOMI KERAKYATAN - Zaenuddin, Zaenuddin (Tahta Media Group, 2026)
This study aims to analyze how social innovation practices in smallholder livestock farming represent the implementation of people-centered economic principles within the national development framework of Asta Cita. The research was conducted in Lombok Timur using a qualitative approach through in-depth interviews, participant observation, and document analysis. The findings reveal that social innovation is collectively constructed through livestock farmer groups, village cooperatives, collective feed purchasing, joint marketing systems, and solidarity funds. These practices emerge as responses to structural constraints such as limited capital access, price fluctuations, and weak bargaining power of small-scale farmers. Social innovation not only improves production efficiency and household income (12–18%) but also strengthens social capital, women’s participation, and community economic resilience. The study demonstrates that people-centered economic principles within the Asta Cita framework can be operationalized through strengthening local institutions and collective participation. Therefore, social innovation in smallholder livestock farming represents an inclusive, participatory, and sustainable model of rural economic development.